Undeveloped Region in Target-Strategies and Potential in Antiviral Drug Discovery - Du, Shaoqing; Liu, Xinyong; Hu, Xueping; Zhan, Peng (Pharmaceutical Fronts, 2025)
Drug resistance is a looming threat to global health security, undermining the effectiveness of current treatments and increasing treatment failures. To address this challenge, it is necessary to explore innovative strategies by identifying new binding mechanisms and targeting previously undeveloped therapeutic avenues. This paper reviewed the potential of leveraging undeveloped domains to combat drug resistance and proposes a range of methodologies to accurately identify those specific targets. There is also an extensive review of the challenges associated with targeting undeveloped areas and strategies to effectively address them. In this process, the application of artificial intelligence (AI) can effectively improve the efficiency of drug design, while appropriate attention should be paid to the physicochemical and drug-like properties of pharmaceutical compounds in the realm of drug discovery. Given the above, focusing on these undeveloped areas could provide a promising pathway to address drug resistance; however, achieving this objective necessitates sustained investigative efforts and inventive approaches.
Keywords: drug resistance; targeting undeveloped sites; antiviral drug design; target-based drug discovery